2018
DOI: 10.1111/jdi.12828
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of serum interleukin‐8 and soluble tumor necrosis factor‐like weak inducer of apoptosis levels in patients with diabetic nephropathy

Abstract: Aims/IntroductionRecent studies suggest that chronic inflammatory responses are important in the development of diabetic nephropathy (DN). Various inflammatory and angiogenesis molecules affect the pathogenesis and progression of DN. Inflammation damages the microcirculation and causes kidney damage. In the present study, we studied changes in interleukin‐8 (IL‐8) and soluble tumor necrosis factor‐like weak inducer of apoptosis (sTWEAK) levels in patients with DN, and investigated the clinical significance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…Many prein ammatory cells, growth regulators, and adhesion factors interact with each other and cross-link, resulting in expansion of the corresponding cascade of in ammation. (13) In recent years, the rapid development of proteomics technology has provided us with new methods and ideas for identifying early diagnostic markers of DN. Proteomics techniques have been used to identify disease-speci c biomarkers and other related proteins in urine.…”
Section: Discussionmentioning
confidence: 99%
“…Many prein ammatory cells, growth regulators, and adhesion factors interact with each other and cross-link, resulting in expansion of the corresponding cascade of in ammation. (13) In recent years, the rapid development of proteomics technology has provided us with new methods and ideas for identifying early diagnostic markers of DN. Proteomics techniques have been used to identify disease-speci c biomarkers and other related proteins in urine.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic polymorphism of IL-8 (IL8-rs4073) showed a strong association in Asian people with DN [195]. Other studies showed elevated circulating IL-8 levels in T2DM patients [193]. A bioinformatic analysis in endothelial precursor cells isolated from patients with T2DM showed that IL-8 and CXCL1 genes were the most expressed molecules in diabetic samples [196].…”
Section: Other Cytokines/proinflammatory Proteins In Dnmentioning
confidence: 99%
“…Among several proinflammatory proteins involved in the development and progression of DN is also the cytokine IL-8, which mainly attracts neutrophils and induces oxidative stress, favoring vascular permeability and endothelial damage in the diabetic kidney [193,194]. Genetic polymorphism of IL-8 (IL8-rs4073) showed a strong association in Asian people with DN [195].…”
Section: Other Cytokines/proinflammatory Proteins In Dnmentioning
confidence: 99%
“…Recent ndings suggest that immune-mediated in ammatory processes play a crucial role in DN. Many prein ammatory cells, growth regulators, and adhesion factors interact with each other and cross-link, resulting in an expansion of the corresponding cascade of in ammation [10]. In recent years, the rapid development of proteomics technology has provided us with new methods and ideas for identifying early diagnostic markers of DN.…”
Section: Discussionmentioning
confidence: 99%